Paternal parenting behaviour and psychological health of adolescents - Yahya, Amira Najiha; Zulkefly, Nor Sheereen; Baharudin, Rozumah (Universiti Putra Malaysia Press, 2018)
Psychological health as one of the most crucial indicators of successful adolescents has received considerable attention in the literature. High prevalence rates of various psychological problems amongst adolescents emphasize the significance of identifying paternal parenting behaviour that may reduce the risk of these problems. However, little attention has been given to how fathers influence their adolescents’ psychological health, especially in an Asian context. To address this issue, this paper presents a thorough discussion of past literature related to paternal parenting behaviour and psychological health of adolescents. The discussion begins with a review related to psychological health, paternal parenting behaviour, and followed by the relationships between paternal parenting behaviour and psychological health. Based on the review of the literature, several research gaps will be addressed at the end of this paper.